Analysis of the Impact of Agglomeration on Regional Economic Growth on Java Island - Warsito, Teguh (Universitas Syiah Kuala, 2023)
Agglomeration is the concentration of economic activity and population in an area. Agglomeration can have positive impacts on economic growth in a region through production efficiency, highly qualified workers, and technological developments in the agglomeration area which will eventually spread to the entire region. However, a high level of agglomeration will have impacts on various urban issues such as the environment issues, traffic congestion, and crime. This research will analyze how the degree of agglomeration, with the variables of population density and percentage of people living in urban areas, affects the economic growth of Java Islands districts and cities, with the quality of human capital as a control variable. There were 119 districts and cities on Java Island that were analyzed with the analysis period from 2016 to 2019 using panel data regression. The research results show that agglomeration significantly and positively influences regional economic growth on Java Island, both as a proxy for population density and the percentage of urban residents living in urban areas. Therefore, the Government needs to develop a series of policies that support agglomeration along with urban planning and environmental policies to minimize the negative impacts of the agglomeration.